2018
DOI: 10.1038/s41424-018-0043-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome of Splanchnic Vein Thrombosis in Cirrhosis

Abstract: IntroductionLittle is known about the long-term outcome of cirrhotic patients with splanchnic vein thrombosis (SVT). This prospective cohort study aimed to describe the clinical presentation, bleeding incidence, thrombotic events, and mortality in patients with SVT associated with cirrhosis.MethodsAmong 604 consecutive patients with SVT enrolled over 2 years, 149 had cirrhosis. Major bleeding, thrombotic events, and all-cause mortality were recorded during a 2-year follow-up. In a subgroup, the degree of recan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 24 publications
4
62
1
Order By: Relevance
“…Patients should therefore not be refused LT, as long as their surgical risk (dictated by additional comorbidities) is acceptable and an adequate transplant benefit can be expected. In the absence of an alternative, effective therapy, candidates for LT with porto‐mesenteric thrombosis nonetheless carry a higher mortality risk while on the waiting list . To sum up, although it is true that mortality after LT is very high in patients with grade 4 PVT, an appropriate transplant benefit may still be achieved in selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Patients should therefore not be refused LT, as long as their surgical risk (dictated by additional comorbidities) is acceptable and an adequate transplant benefit can be expected. In the absence of an alternative, effective therapy, candidates for LT with porto‐mesenteric thrombosis nonetheless carry a higher mortality risk while on the waiting list . To sum up, although it is true that mortality after LT is very high in patients with grade 4 PVT, an appropriate transplant benefit may still be achieved in selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, this does not agree with an increasing body of data on the impact of recanalization during anticoagulation therapy. Recanalization during anticoagulant therapy is related to improved event‐free survival after adjustment for the severity of liver disease and portal hypertension, improved liver function tests as well as decreased mortality, particularly in patients with the most severe liver disease . It is frustrating to note that no predictors for the resolution of portal vein thrombus have been identified .…”
Section: Portal Vein Thrombosis In Patients With Cirrhosismentioning
confidence: 99%
“…Not surprisingly multivariate analyses in these retrospective observational studies showed significant differences between patients who received anticoagulants and those who did not. In particular, a lower proportion of past variceal bleeding or cavernoma, lower blood urea levels, a smaller proportion of alcoholics, severe liver disease or cavernoma were found as well as an increased proportion of women or non‐specific beta‐blockers and a higher proportion of involvement of the superior mesenteric vein or multiple venous sites . These factors were not taken into account in the 2017 meta‐analysis …”
Section: Recanalization Of the Thrombosed Portal Veinmentioning
confidence: 99%
See 2 more Smart Citations